Volatile Oils from Natural Plants: Promising Penetration Enhancers for Biological Barriers - Ma, Xinyu; Jin, Yu; Wang, Miao; Zong, Shiyu; Cheng, Yunlong; Zhang, Hong; Wu, Wei; Lu, Yi; Li, Ye; Wang, Chunliu (Pharmaceutical Fronts, 2025)
Drug delivery often faces challenges from biological barriers, including the skin and mucosa. Penetration enhancers (PEs) are commonly employed to improve the delivery of poorly permeable drugs. Among them, volatile oils derived from natural plants have emerged as promising candidates due to their rapid action, minimal side effects, and high efficiency. This paper provides a brief introduction to biological barriers and highlights the potential of volatile oils as PEs and their underlying mechanisms. Their role in improving transdermal and transmucosal drug delivery has been explored by a comprehensive review of recent research, which provides valuable insights into their future application in pharmaceutical formulations.
Keywords: volatile oils; penetration enhancer; biological barriers; transdermal delivery; mucosal delivery